A high-frequency financial conditions index for Norway - Frida Bowe; Karsten R. Gerdrup; Nicolò Maffei-Faccioli; Helene Olsen (Norges Bank, 2023)
We have constructed a financial conditions index for Norway (FCIN). The FCIN offers a daily update on Norwegian financial conditions based on data from January 2003 on bank lending rates, bond spreads, the foreign exchange market, the stock market and the housing market. The index is constructed by the use of principal component analysis and has an average value of zero and a standard deviation of one. A positive value indicates that financial conditions are tighter than the historical average, while a negative value suggests that financial conditions are looser than the historical average. The FCIN is constructed to provide real time insight into financial conditions for the Norwegian economy beyond what is already included in the policy rate and market policy rate expectations. Here we depart from other studies which typically aim at assessing financial conditions more broadly. The index is meant to complement monetary policy analyses and improve our assessments of economic activity.
hdl:11250/3042516
Keywords: C32; C53; E32; E44; 330; Financial conditions index; forecasting; principal component analysis; financial shocks